Effects of estradiol and progestogens on human breast cells: Regulation of sex steroid receptors - Fang-Ping Chen; Mei-Hua Chien; Huang-Yang Chen; Ting-Shuo Huang; Yuet-Tong Ng (Elsevier, 2013)
Objectives: To examine the effects of 17β-estradiol (E2) and progestogens, used in hormone therapy, on estrogen receptors (ER), progesterone receptors (PR), and human breast tumor cell growth. Materials and methods: MCF-7 cells were incubated in pure E2 (1 nM and 10 nM) as well as in E2 in conjunction with 10 nM progestogens, including progesterone (P4), medroxyprogesterone acetate (MPA), norethisterone acetate (NET), and cyproterone acetate (CPA). Cell proliferation, apoptosis, expression of caspase-3, and both ER and PR isoforms were evaluated. Results: Caspase-3 was significantly diminished in cultures with only E2, whereas ERα significantly increased. A significant increase of caspase-3 in addition to the entire abolishment of E2-induced augmentation of ERα was observed in 1 nM E2 plus MPA and 10 nM E2 plus NET, whereas PR isoform B (PRB) was significantly increased. The ratios of apoptosis: proliferation significantly increased in 1 nM E2 plus progestogens (except P4) and 10 nM E2 plus NET. The changes of the PRA/PRB ratio were inversely related to the changes of the apoptosis to proliferation ratio. Significant increase of ERβ and PRB was noted in the E2 plus MPA or NET, in addition to a significant increase of ERα and decrease of PRA in the E2 plus CPA, as well as an increase of ERα and decrease of PRA and PRB in the E2 plus P4. Conclusions: The combination of E2 and various progestogens resulted in diverging effects on ERs and PRs expressions, which induced different effects on MCF-7 cell growth. Compared with P4, aberrant hormone and biological activity of synthetic progestin, by way of altered receptor expression, may be an important factor in affecting breast cell growth.